Gene therapy for trigeminal pain in mice - Tzabazis, Alexander Z. (2014)
The aim of this study was to test the efficacy of a single direct injection of viral vector encoding for encephalin to induce a widespread expression of the transgene and potential analgesic effect in trigeminal behavioral pain models in mice. After direct injection of HSV-1 based vectors encoding for human preproenkephalin (SHPE) or the lacZ reporter gene (SHZ.1, control virus) into the trigeminal ganglia in mice, we performed an orofacial formalin test and assessed the cumulative nociceptive behavior at different time points after injection of the viral vectors. We observed an analgesic effect on nociceptive behavior that lasted up to 8 weeks after a single injection of SHPE into the trigeminal ganglia. Control virus injected animals showed nociceptive behavior similar to naïve mice. The analgesic effect of SHPE injection was reversed/attenuated by subcutaneous naloxone injections, a μ-opioid receptor antagonist. SHPE injected mice also showed normalization in withdrawal latencies upon thermal noxious stimulation of inflamed ears after subdermal complete Freund’s adjuvans injection indicating widespread expression of the transgene. Quantitative immunohistochemistry of trigeminal ganglia showed expression of human preproenkephalin after SHPE injection. Direct injection of viral vectors proved to be useful for exploring the distinct pathophysiology of the trigeminal system and could also be an interesting addition to the pain therapists’ armamentarium.